Holocene fire in relation to environmental change and human activity reconstructed from sedimentary charcoal of Chaohu Lake, East China. (25th February 2019) - Wu, Li; Li, Linying; Zhou, Hui; Wang, Xinyuan; Zhang, Guangsheng
Abstract: Through analysis of the concentration of different-sized charcoals and magnetic susceptibility of the CH-1 core from Chaohu Lake, East China during the Holocene, the features of fire in relation to environmental change in the charcoal record and the effect of human activities were revealed. Between 9870 and 6040 cal yr BP, the climate was still relatively dry, although it was becoming warmer and wetter. The relatively dry climate apparently created favorable conditions for natural fires to occur, which suggests that the charcoal concentration was high. The warmest and wettest period was from 6040 to 2170 cal yr BP during the Holocene, and very little charcoal was found in the core, because the high precipitation during this period apparently suppressed natural fires. However, human activities increased the fire frequency during the cultural phase. Archaeological investigations indicate that a large number of Neolithic and historic sites, including the Lingjiatan cultural sites (5600–5300 cal yr BP), were distributed around Chaohu Lake. As a result, value peaks in the charcoal concentration were shown. After 2170 cal yr BP, the climate became drier and cooler, and conditions were once again favorable for fires to occur naturally. The concentration of charcoal in the core greatly increased and showed the greatest levels of fire activity, which was related to both the drier climate and the enhanced human activities. The water level of Chaohu Lake reached a minimum in this period, as the lakebed was possibly exposed and formed the substrate for ancient sites, such as the flourishing Juchao state (2090–1710 cal yr BP). During the most recent 200 years, the amount of charcoal concentration sharply decreased, and fire occurrence disappeared gradually because there was not enough biomass in the Chaohu Lake basin.